THE EFFECT OF INDIGOFERA SP FLOUR FEED ON PHYSIOLOGICAL RESPONSE OF FAT TAIL SHEEP - Rosmayanti, Pratiwi; Sudrajat, Deden; Malik, Burhanudin (Jurnal Peternakan Nusantara, 2019)
Sheep is a small ruminant llivestock that area mostly raised by farmers in Indonesia fat tailed sheep (DEG) is one of the genetic resources of livestock that has  economics, scientifics and socio-cultural values and has the potential; to be used to meet the needs of animal protein for humans. This study aimed to examine the effect of indigofera sp flour feeding on the physiological response of fat tail rams. The design used was a completely randomized design with the following treatments: control feed without administration of indigofera sp flour (P0), commercial feed + 10% Indigofera sp flour (P1), Commercial feed +20% Indigofera sp flour (P2). The treatments was given to male fat-tailed sheep with body weight (30 kg) and uniform age (1,5 years), healthy and not disabled. The variables observed were body temperature, respiration rate, heart rate, and feed consumption. The treatments of giving Indigofera sp flour to the ration was estimated to have a significant effect (respiration rate, heart rate and body temperature) from the normal limit compared to thr treatments of fat tail rams without administration of Indigofera sp flour.Key words: fat tailed sheep, Indigofera sp flour, physiological response